Resveratrol and Spirulina: Nutraceuticals that Potentially Improving Cardiovascular Disease - Wang, Yifan; Ocampo, Maria Fides; Rodriguez, Bianca; Chen, Jiwang (Journal of Cardiovascular Medicine and Cardiology, 2020)
Resveratrol (3,5,4’-trihydroxy-trans-stilbene) is an extensively studied nutraceutical with several proposed health benefits, including cardio protection, antimetabolic syndrome, and antiatherogenic effects. It was brought to popularity through the proposed “French Paradox” and the consumption of red wine. It has been shown to down regulate the activation of numerous inflammatory and oxidative stress markers with therapeutic potentials. Spirulina (Arthrospira platensis), on the other hand, is a highly nutritional nutraceutical that has not been sufficiently studied. However, several in vitro and animal studies point to its hypolipidemic and antihypertensive properties, which are similar to resveratrol. Although resveratrol and Spirulina both constitutes functional foods with potential therapeutic effects on several cardiovascular diseases, there are few compelling clinical evidence to support their applications in human patients. This warrant further evaluation in clinical trials. This article reviews and evaluates the beneficial effects of the two different nutraceuticals in order to demonstrate their potential in clinical application in patients with cardiovascular diseases.